Pour une mésoéconomie de l’émergence d’une bioéconomie : représentations, patrimoines productifs collectifs et stratégies d’acteurs dans la régulation d’une chimie doublement verte - Nicolas Béfort (Revue de la Régulation)
This thesis analyses the emergence of a new economic space from a mesoeconomic regulationist and evolutionist approach. This space has been called "bioeconomy" by the actors after divergent and conflictual interpretations of this concept. This economic space differs from the traditional ways of representing the division of labour into sectors (chemistry, agriculture, energy). The actors involved in seeking to define this space are reconstructing these sectors into an original and specific field, which is built on the use of biobased plant, animal and algal renewable resources. These actors consider themselves to be becoming the "industry of industries". Thus, instead of providing end products, they produce intermediates for agro- or chemical industries, materials or energy. The field does not cover photovoltaic electricity. Therefore, bioeconomy is a recomposition of the relationships between agriculture and chemistry in which the former becomes the supplier for the latter. We use the concept of the regimes of production of knowledge and of economic activity to describe the diversity of the technological promises made by the actors involved. We show, therefore, that bioeconomy cannot be reduced to the biotechnological revolution. Three broad views of bioeconomy emerge. At a deeper level, we present here three case studies to illustrate this diversity. The actors are weighed down by an "economy of promises" based on their own productive heritages that they are trying to reproduce and project into the future. This leads them to problematize the bioeconomy space in order to determine their resource allocations.